2005
DOI: 10.1172/jci24594
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptors   and   regulate renin expression in vivo

Abstract: The renin-angiotensin-aldosterone system controls blood pressure and salt-volume homeostasis. Renin, which is the first enzymatic step of the cascade, is critically regulated at the transcriptional level. In the present study, we investigated the role of liver X receptor α (LXRα) and LXRβ in the regulation of renin. In vitro, both LXRs could bind to a noncanonical responsive element in the renin promoter and regulated renin transcription. While LXRα functioned as a cAMP-activated factor, LXRβ was inversely aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 40 publications
4
73
1
2
Order By: Relevance
“…This possibility needs to be validated in future studies using LXRα-null mice. It has been shown that acute LXR activation induces a transient increase in renin transcription in the juxtaglomerular cells (32), but its chronic activation remarkably suppresses the expression of renin, AT1R, and angiotensin 1-converting enzyme 1 (ACE) in the heart and kidney following isoproterenol treatment (52). In agreement with the inhibitory effect of LXRs on local RAS, we found that TO901317 treatment remarkably suppressed urinary renin, an index of the intrarenal RAS (35,53).…”
Section: Induction Of Diabetes Insipidus and Suppression Of Renal Prrsupporting
confidence: 74%
“…This possibility needs to be validated in future studies using LXRα-null mice. It has been shown that acute LXR activation induces a transient increase in renin transcription in the juxtaglomerular cells (32), but its chronic activation remarkably suppresses the expression of renin, AT1R, and angiotensin 1-converting enzyme 1 (ACE) in the heart and kidney following isoproterenol treatment (52). In agreement with the inhibitory effect of LXRs on local RAS, we found that TO901317 treatment remarkably suppressed urinary renin, an index of the intrarenal RAS (35,53).…”
Section: Induction Of Diabetes Insipidus and Suppression Of Renal Prrsupporting
confidence: 74%
“…This finding was confirmed recently using a mouse in vivo model. 6 Both LXR-␣ and LXR-␤ were shown to be regulators of renin transcription. Renal expression of LXR-␣ was found confined to JG cells (Figure 2).…”
Section: Liver X Receptorsmentioning
confidence: 99%
“…Our mice exhibited varying sensitivities to STZ, which left the number of animals in some groups lower than anticipated. We did not perform an exhaustive survey of the RAS; however, it is notable that Lxrα/β −/− mice have previously been shown to have a blunted response to isoprenaline, suggesting that Lxrα/β −/− mice would be protected against (not susceptible to) hypertension [46]. DMHCA was very effective at decreasing circulating cholesterol and triacylglycerol levels with additional beneficial effects on liver lipid levels.…”
Section: Discussionmentioning
confidence: 97%